The Mycobacterium tuberculosis CRISPR-Associated Cas1 Involves Persistence and Tolerance to Anti-Tubercular Drugs. (2nd April 2019) - Wei, Jiawei; Lu, Nan; Li, Zhiying; Wu, Xuanyan; Jiang, Tao; Xu, Li; Yang, Chun; Guo, Shuliang
Abstract : Tuberculosis remains one of the leading causes of death worldwide. Even if new antitubercular drugs are currently being developed, the rapid emergence and spread of drug-resistant strain remain a severe challenge. The CRISPR associated proteins 1 (Cas1), a most conserved endonuclease which is responsible for spacer integration into CRISPR arrays, was found deleted in many specific drug-resistant strains. The function of Cas1 is still unknown in Mycobacterium type III-A CRISPR family. In this study, the Cas1 (Rv2817c) defect was found in 57.14% of clinical isolates. To investigate the function of Cas1 in new spacer acquisition, we challenged Bacillus Calmette–Guérin (BCG) with a mycobacteriophage D29. Newly acquired spacer sequence matches D29 genome was not found by spacer deep-sequencing. We further expressed Cas1 in recombinant Mycobacterium smegmatis . We found that Cas1 increased the sensitivity to multiple anti-tuberculosis drugs by reducing the persistence during drug treatment. We also showed that Cas1 impaired the repair of DNA damage and changed the stress response of Mycobacterium smegmatis . This study provides a further understanding of Cas1 in Mycobacterium tuberculosis complex (MTBC) drug-resistance evolution and a new sight for the tuberculosis treatment.